Implications for the diagnosis of aspiration and aspergillosis in critically ill patients with detection of galactomannan in broncho-alveolar lavage fluids - Dubler, Simon; Etringer, Michael; Lichtenstern, Christoph; Brenner, Thorsten; Zimmermann, Stefan; Schnitzler, Paul; Budeus, Bettina; Rengier, Fabian; Kalinowska, Paulina; Hoo, Yuan Lih; Weigand, Markus A. (Scientific reports, 2025)
Invasive infections with Aspergillus fumigatus in ICU patients are linked to high morbidity and mortality. Diagnosing invasive pulmonary aspergillosis (IPA) in non-immunosuppressed patients is difficult, as Aspergillus antigen (galactomannan [GM]) may have other causes. This retrospective study analyzed 160 ICU surgical patients with positive GM in broncho-alveolar lavage fluid (BALF), classifying them based on AspICU criteria for suspected IPA (pIPA) or aspiration. Patients with pIPA had higher disease severity than those with aspiration, including higher dialysis rates, organ transplantation, corticosteroid use, and Sequential Organ Failure Assessment (SOFA) score. Aspergillus culture was positive in 47.0% of pIPA cases but only 2.6% of aspiration cases (p < 0.001). SOFA score at first positive GM in BALF independently predicted 28-day mortality. In surgical patients with a positive GM in BALF, aspiration is more likely if there’s no corticosteroid therapy, negative Aspergillus culture, and a history of aspiration events. Diagnosis of pIPA requires Aspergillus culture or prior corticosteroid therapy in this cohort of critically ill patients.